Niveles de Hemoglobina y Hematocrito en usuarios mayores de 15 años atendidos en el Centro de Salud Víctor Larco, Trujillo, marzo, 2018 - Veloz Bazán, Sandra Ydalina (2018)
In our thesis, the objective was to determine hemoglobin and hematocrit levels in users over 15 years of age served at the Víctor Larco Health Center, Trujillo, march, 2018. In our study, 54 blood samples were taken from people over 15 years of age. The anthropometric measurements were made using the variables: height (cm) and weight (kg), hemoglobin (cyanometahemoglobin method), hematocrit (microhematocrit) and subject to BMI, sex and age with prior consent and assent of the users. The mean values were hemoglobin 13.92; hematocrit 40.72; BMI 26.56 and age 41.24. It was found that 3.70% of users older than 15 years have high hemoglobin, 66.6% have normal hemoglobin and 29.63%; he has low hemoglobin It was also found that 11.1 %% of users older than 15 years have high hematocrit, 61.1 %% have normal hematocrit and 27.77%; has a low hematocrit It is concluded that statistically there is no correlation between the values of Hemoglobin and sex, age and BMI